A general synthetic method towards conjugated microporous polymers with ordered bicontinuous mesostructures. Issue 32 (3rd April 2023) - Yang, Qiqi; Liu, Yamei; Xiang, Luoxing; Zhang, Jiacheng; Yin, Yucheng; Xu, Fugui; Mai, Yiyong
Abstract : This study demonstrates a universal nanocasting approach for the synthesis of novel conjugated microporous polymers (CMPs) with bicontinuous architectures. Abstract : This work demonstrates a universal approach, based on the self-assembly of block copolymers, for the synthesis of novel conjugated microporous polymers (CMPs) with bicontinuous mesostructures. Three hexaazatriphenylene (Aza)-fused CMPs (Aza-CMPs) with double diamond structures were synthesized. The study broadens the spectrum of bicontinuous porous materials and opens a new route for synthesizing CMPs with new topologies.